2017
DOI: 10.1016/j.ijporl.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

An innovative approach to improve ear, nose and throat surgical access for remote living Cape York Indigenous children

Abstract: This innovative approach to a health system crisis enabled successful ENT surgical and hearing outcomes in 16 children, whose waitlisted time grossly exceeded state health recommendations. Using private health facilities funded by a health partnership, while unlikely to be a suitable model of care for routine service delivery; may be applied as an adjunct service model when blockages and delays lead to sub-standard service provision. This approach may be applicable to other health care facilities when facing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(59 citation statements)
references
References 47 publications
0
59
0
Order By: Relevance
“…Further improvements have also been demonstrated for patients due to improved efficiencies, such as shorter wait times for ENT services, and less time lost from travel or missed appointments . A recent Australian study on ENT surgery, using TeleHealth for post‐operative review, identified a minimum cost saving of AUD$21 664 . TeleMedicine has been used extensively for ENT pre‐surgery planning and post‐surgical review across remote areas of Alaska .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further improvements have also been demonstrated for patients due to improved efficiencies, such as shorter wait times for ENT services, and less time lost from travel or missed appointments . A recent Australian study on ENT surgery, using TeleHealth for post‐operative review, identified a minimum cost saving of AUD$21 664 . TeleMedicine has been used extensively for ENT pre‐surgery planning and post‐surgical review across remote areas of Alaska .…”
Section: Discussionmentioning
confidence: 99%
“…The study aims to identify the least‐cost approach by funding source. We compare the costs of standard service delivery (model 1), against the service model recently described (model 2), with an alternative model of surgical access and care that includes ear and hearing health (EH) team and TeleHealth for pre‐post‐surgical reviews (model 3). Costs are assessed from two viewpoints: (1) health system perspective, and (2) patients and their families including travel out‐of‐pocket expenses.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations